Integrating Science and Entrepreneurial Character Among Islamic Boarding School Students Through an Integrated Agribusiness Model - Afiful Ihwan; Wahidmurni; Jamiluddin Yacub (Jurnal Penelitian Pendidikan IPA, 2026)
This study analyzes the integration of scientific knowledge and entrepreneurial character development among santri (Islamic boarding school students) through an integrated agribusiness model at two pesantren in East Ogan Komering Ulu, Indonesia. Using a qualitative case study approach with interviews, observation, and document analysis, findings reveal that both institutions systematically combine scientific agricultural practices—such as hydroponics, organic cultivation, and sustainable resource management—with Islamic ethical principles like amanah (trustworthiness) and muamalah fiqh. Three core strategies emerged: value-infused mentorship, reflective practice, and community-engaged learning, which collectively cultivate a distinctive "santripreneur" identity wherein scientific literacy, economic agency, and spiritual accountability mutually reinforce one another. Santri demonstrated enhanced entrepreneurial self-efficacy, innovation orientation, evidence-based decision-making, and ethical reasoning. The study concludes that integrated agribusiness models effectively internalize entrepreneurial character when grounded in experiential learning, science-based pedagogy, and value-based instruction. However, scalability requires addressing systemic constraints—including technological access, market linkages, and educator capacity—through coordinated multi-stakeholder support. These insights offer a replicable framework for Islamic educational institutions seeking to cultivate ethically grounded, scientifically literate, and economically resilient graduates capable of contributing to sustainable rural development.